Effects of cantilever projections on seismic performances of RC buildings - Ishwor Karki,; Hari Ram Parajuli, (Journal of Innovations in Engineering Education, 2023)
There is a common practice of extending the cantilever beams/slabs on the upper floors of a building in Nepal either to increase the room size or for aesthetic purposes. It ignores the increased seismic effects due to asymmetry. In most cases, reinforced concrete frame structures are designed without cantilevers. However, in reality, it’s not always the same. Hence, the assumed effects during the structural analysis do not reflect the real behavior of the built structural system. This study aims at presenting the effects of cantilever projections in the seismic response parameters of regular RC frame building. For this, 3 and 5 story regular RC buildings along with 3 feet, 4 feet, 5 feet and 6 feet cantilever projections on one and two facades are selected resulting to a total of 18 models. All the models are analyzed using Response Spectrum Analysis method. The results demonstrate that the cantilever projections in regular building cause the significant increment in the seismic response parameters. The fundamental time period is increased by 10.93%, the base shear by 19.67%, the inter-story drift ratio by 52.57% and the overturning moment by 20.36% upon increase in mass by 19.69% due to cantilevers. The torsional moment in column is increased by 3.53 times and bending moment in column by 1.5 times whereas the cantilever deflection has exceeded the allowable limit. Therefore, proper engineering analysis and design is essential for cantilevers to ensure the overall safety and performance of the structure during seismic events.